Pendidikan Karakter Berbasis Sekolah/Madrasah - Mukhtar Zaini Dahlan (LP3M Universitas Islam Zainul Hasan Genggong, 2016)
Changing bad habits is not easy even with a strong determination, but the bad habits it more effectively be replaced with good habits dengann driven attentive and consistent and strong will. Knowingly or not, need all the factors determining the success of character education in the school / Madrasah There is a strong commitment (earnest) of principals, teachers, and educational facilities. Conditioning their custom programmed and integrated with universal values. Teachers, principals, and other educational tools should be an example (modeling). Performed with consistently and continuous (sustainable) .Always do motivation and evaluation of the use of models and methods